The Effect Of Democratic Leadership Style And Work Motivation On Employee Performance Through Job Satisfaction At The Office Of The District Of West Binjai - Bobby Arisandi; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the influence of Democratic Leadership Style and Work Motivation on Employee Performance by considering the role of Job Satisfaction as an intervening variable at the West Binjai District Office. Democratic leadership style allows employee participation in decision making and is expected to increase motivation and job satisfaction, which ultimately has a positive effect on their performance. This study uses a quantitative approach with data obtained through a survey of employees, then analyzed using the Partial Least Squares (PLS) method. The results of the analysis show that Democratic Leadership Style has a negative but significant effect on Job Satisfaction with a T-Statistic value of 2.562 and a P-Value of 0.000, while its effect on Employee Performance is positive and significant with a T-Statistic value of 2.854 and a P-Value of 0.006. Work Motivation has a positive and significant effect on Job Satisfaction with a T-Statistic value of 5.971 and a P-Value of 0.000, but shows a negative effect on Employee Performance directly. Job Satisfaction itself is proven to have a positive and significant influence on Employee Performance with a T-Statistic value of 10.033 and a P-Value of 0.000. The analysis of indirect effects shows that both Democratic Leadership Style and Motivation have a significant influence on Employee Performance through Job Satisfaction as a mediating variable. This finding confirms the importance of Job Satisfaction in strengthening the influence of Democratic Leadership Style and Motivation on Employee Performance. Suggestions are given to the West Binjai Sub-district Office to improve leadership methods and increase employee motivation in order to achieve more optimal performance.